SIFAT PEMESINAN ENAM JENIS KAYU INDONESIA - Bakir Ginoga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
The quality of machining properties of six Indonesian wood species, i.e. meranti merah (Shorea selanica BI .), medang lesa (Cinnamomum parthenoxylon Meissn.), dahu (Draconto-melon mangiferum BI.), kaya (Khaya anthoteca Cdc.), bawang (Melia excelsa Jack.), and merawan (Hopea odorata , from Darmaga Experimental forest, has been investigated. The testing was carried out based on air dried specimen. The results revealed that the planing and moulding quality varies from good (II) to very good classes(1); turning and sanding belong to good class (II). while boring quality varies from medium (III) to good (II) classes.